2020
DOI: 10.1111/vru.12939
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography with Hounsfield unit assessment is useful in the diagnosis of liver lobe torsion in pet rabbits (Oryctolagus cuniculus)

Abstract: Clinical signs of liver lobe torsion in rabbits are often nonspecific and mimic those that are also generally detected with gastrointestinal stasis. Nonspecific clinical signs may result in pursuit of full‐body imaging such as computed tomography (CT). The aim of this multicenter, retrospective, case series study was to describe CT findings of liver lobe torsion in a group of rabbits. Computed tomography studies of six rabbits with confirmed liver lobe torsion by surgery or necropsy were evaluated. The caudate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(43 citation statements)
references
References 20 publications
(61 reference statements)
2
41
0
Order By: Relevance
“…In a previous study from our hospital, CT was found to be highly sensitive and specific for LLT in rabbits and required only injectable sedation to perform. Computed tomography required similar or even less time than abdominal ultrasound to reach a diagnosis 23 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study from our hospital, CT was found to be highly sensitive and specific for LLT in rabbits and required only injectable sedation to perform. Computed tomography required similar or even less time than abdominal ultrasound to reach a diagnosis 23 …”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography required similar or even less time than abdominal ultrasound to reach a diagnosis. 23 A critical finding from the cadaver study that was importance of close proximity of the paracostal incision to the rib cage. A linear dorsoventral incision limited cranial exposure of the caudate liver lobe, whereas a curvilinear incision along the ventral edge of the ribs maximized exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinicopathologic findings commonly show anaemia together with hepatic enzyme elevation and azotaemia 15 . Abdominal ultrasonography and, more recently, contrast‐enhanced computed tomography (CECT) are sensitive diagnostic imaging modalities for this condition 14,15 . Improved survival appears to be associated with medical stabilisation followed by surgical management 12,13,15,17,23–26 .…”
Section: Introductionmentioning
confidence: 99%